One year of living with COVID 19 an assessment of how ADB members fought the pandemic in 2020. (Metro Manila, Philippines Asian Development Bank, 2021)
The report analyzes the specific measures taken, classified into liquidity support, credit creation, long term lending, equity support, and health and income support. The analysis focuses on the financial statement effects of a given measure, in particular: (i) who, if anyone, bears the financial burden of the measure and in what form?; and (ii) does the measure create more debt or more income (e.g., net worth or equity, other things being equal) for the recipients.
Keywords: Covid 19, Disease; Stabilization policy; Public loan program; Electronic books